Analysis of Freight Modal Shift Potential on Railway Infrastructure Development for Cross-Border Trade under the Belt and Road Initiative Strategy - Klairung Ponanan; Sirikarn Chansombat (Science & Technology Asia, 2024)
The Chinese government has developed transport infrastructure rapidly under the Belt and Road Initiative (BRI) strategy. The development of transportation infrastructure has been affected by the transportation aspect of ASEAN countries, especially Thailand. Therefore, this study aims to forecast the freight transportation demand of each mode that will be shifted from the existing transportation mode to the railway mode, specifically in the case of a potential new railway route that can link to the China-Laos railway. A questionnaire was used to collect the data for the 180 samples, which sample group consists of entrepreneurs who are related to freight transportation. Then the Mode Choice Model was generated to forecast freight transportation demand, which is the route that can be connected with the China-Laos railway. The results show that the mode shift of freight transportation is separated into 2 sub-models for the decision-making of entrepreneurs on transportation mode, which consist of (1) entrepreneurs who invest in transportation infrastructure by themselves, and (2) entrepreneurs who do not invest in transportation infrastructure by themselves. The group of entrepreneurs belonging to the (1) sub-model will not change the current transportation mode to rail mode on the railway route due to their investment cost of the infrastructure, which this supposed to be energy products. In the group of entrepreneurs that belongs to (2) sub-model, some entrepreneurs will change the current transportation mode to rail mode on the railway route, which this supposed be to the consumer products.